Structural Policies and Growth A Non-Technical Overview - de Serres, Alain (OECD Publishing, 2003)
In contrast to what has happened throughout the 1960s and 1970s, some of the largest EU countries and Japan are no longer closing the income gap vis-à-vis the United States. Worse, the gap may even be widening since the mid-1990s. While in the case of Japan the gap in GDP per capita is essentially due to the lagging performance in labour productivity, the European Union is trailing mainly in terms of labour resource utilisation, reflecting both lower employment rates and fewer hours worked. This paper provides a brief overview of the main structural factors thought to have contributed to differences in the degree of labour resource utilisation, as well as in the intensity of physical and human capital use and in the pace of technological progress. In doing so, it provides a set of performance and policy indicators which can be used to assess progress achieved in structural reform ...
Keywords: Economics